Bioinspired kinetic architecture and adaptive component desing proposal - Atawula, Aisa (My University, 2016)
Architecture are structures of defined spaces that protect people and their belongings from the exterior environment, among which are the harsh weather conditions, such as wind, rain, and excess sun radiation. Kinetic architecture is the new design method to achieve sustainability by adapting to variable environmental conditions. Previous researches about kinetic architecture mostly considered to use mechanical components and systems for actuation and transformation. Designing kinetic architecture is at the crossroad of either utilizing revolution of shape changing materials with strategies from nature or continue using existing mechanical approaches. In this thesis, adaptation principles from leaves stomata is applied to propose adaptive component that can accommodate to the environmental changes with less energy consumption by utilizing shape changing materials. In this research alternative design strategies for kinetic adaptable building systems have been investigated based on bioinspired design approach. The internal environment of an organism is kept constant within certain limits by regulating mechanisms called homeostasis. Investigating and analyzing these strategies enables architects and engineers to transfer these strategies to kinetic building design. It is proposed that the implementation of successful adaptation strategies inspired from nature can result in adaptable building systems that “behave” as living organisms that accommodate to the dynamic environmental changes. Plants are recognized as examples of kinetic systems that perform mobility with minimal energy use, due to the fiber elasticity composition, and integrating sensing and actuating capabilities into their system. The stomata of plants leaves are chosen as role model for adaptive component which is capable of adapting to CO2 level change in space and temperature fluctuation to provide interior environment comfort for users. This adaptive component is most effective in environments where demand control ventilation is needed such as classrooms, theaters, auditoriums, data centers, stadiums and mosques where the occupancy is intermittent and often well below the maximum design occupancy. Working principles of the adaptive component and three application scenario is discussed in detail and its environmental benefits is explained. Another aim of this research is to explore alternative material systems for actuation of kinetic systems. The development of shape changing materials influenced the design of kinetic architecture. New possibilities of applying shape changing materials in modular systems for architectural skins that respond to various environmental conditions is explored. Shape memory alloy is utilized for adaptive component due to its kinetic behavior in lower temperature and shape memory effect. It is concluded from the research that through utilizing shape changing materials for kinetic architecture systems bioinspired adaptive sustainable buildings could be achieved by transferring plants adaptation principles into architectural design solutions.

Mimari insanları ve onların eşyalarını dış ortamdan, rüzgar, yağmur ve yoğun güneş ışığı gibi sert iklim koşullarından koruyan strüktürler olarak tanımlanır. Kinetik mimari çeşitli çevresel şartları adapte ederek sürdürülebilirliğe erişmek için kullanılan yeni tasarım yöntemidir. Kinetik mimari ile ilgili önceden yapılan çalışmalar sıklıkla harekete geçirme ve kinetik dönüşüm için mekanik bileşenleri ve sistemleri kullanmayı kapsamaktadır. Kinetik mimariyi tasarlamak ya doğadan biçim değiştiren malzemelerin devriminden; ya da var olan mekanik yaklaşımlardan faydalanır. Bu tezde, yaprak gözeneklerinden adaptasyon prensipleri biçim değiştiren malzemelerden faydalanılarak az enerji tüketimiyle çevresel değişimlere uyum sağlayabilen, uyarlanabilir bileşen sunmak için uygulanır. Bu araştırmada biyolojiden esinlenmiş tasarım yaklaşımlarına dayanarak kinetik uyarlanabilir bina sistemleri için alternatif tasarım stratejileri araştırılmıştır. Bir organizmanın iç ortamı homeostasis denilen düzenleyici mekanizmalarla çevredeki çeşitliliğe rağmen belirli limitlerde sabit tutulur. Bu stratejilerin araştırılması ve analizi mimar ve mühendislerin bu stratejileri kinetik bina tasarımına transfer etmelerini sağlar. Doğadan esinlenen başarılı uyum stratejilerinin uygulanması, uyum sağlayabilen bina sistemlerinin yaşayan organizmalar ya da dinamik çevresel değişimlere uyum sağlayabilen doğal sistemler gibi davranmasını sağlar. Bitkiler lifli elastiklik kompozisyonlarından dolayı, minimum enerji kullanımıyla mobilete sağlayan kinetik sistemlere örnektir, ve sezme ve harekete geçirme kapasitelerini sistemlerine entegre edebilirler. Bitkilerin gözenekleri, mekandaki kullanıcılara iç ortam konforu sağladığı, CO2 ve sıcaklık değişimlerine adapte olabildikleri için uyarlanabilir bileşen için rol model olarak seçilmiştir. Bu uyarlanabilir bileşen modülü talep kontrollü havalandırmaya ihtiyaç duyulan sınıf, tiyatro, oditoryum, bilgi merkezi, stadyum ve cami gibi kullanımın aralıklı olduğu ve genellikle maksimum tasarım kullanımının olduğu ortamlarda en etkilidir. Uyarlanabilir bileşeninin çalışma prensipleri ve üç uygulana senaryosu detaylı olarak tartışılmış ve çevresel katkıları açıklanmıştır. Bu araştırmanın bir diğer amacı da kinetik sistemlerin uyarlanması için alternatif malzeme sistemlerini keşfetmektir. Biçim değiştiren malzemelerin gelişimi kinetik mimarinin tasarlanmasını da etkiler. Mimari kabuklar için biçim değiştiren malzemelerin uygulanmasının modüler sitemlerde sağladığı, çeşitli çevresel durumlara yeni olanaklar ortaya çıkarılmıştır. Şekil bellekli alaşım düşük sıcaklıktaki kinetik davranışı ve biçim hafıza etkisi için ADAPTIVE COMPONENT kullanılır. Bu araştırmadan kinetik mimari sistemler için biçim değiştiren malzemelerden faydalanılması, biyolojiden esinlenmiş uyarlanabilir sürdürülebilir binaların bitkilerin uyum prensiplerinin mimari tasarım çözümlerine dönüştürülmesi ile başarılabileceği sonucuna varılabilir.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Keywords: Kinetik mimari; Biyolojiden esinlenmiş tasarım; Biçim değiştiren malzeme; Uyarlanabilir bileşen; Talep kontrollü havalandırma; Biçim hafıza alaşımı; Kinetic architecture; Adaptability; Bioinspired design; Shape changing materials; Adaptive component; Demand controlled ventilation; Shape memory alloy